Multidisciplinary approach for the aesthetic treatment of maxillary lateral incisors agenesis: thinking about implants? - de Avila, Erica Dorigatti [UNESP]; de Molon, Rafael Scaf [UNESP]; Mollo Junior, Francisco de Assis [UNESP]; Borelli de Barros, Luiz Antonio [UNESP]; Capelozza Filho, Leopoldino; Cardoso, Mauricio de Almeida; Cirelli, Joni Augusto [UNESP] (Elsevier B.V., 2012)
Missing maxillary lateral incisors create an esthetic problem with specific orthodontic and prosthetic considerations. Implants are commonly used to replace congenitally missing lateral incisors in adolescent orthodontic patients. However, an interdisciplinary approach should be observed during the diagnosis, prognosis, and treatment plan to provide a result with good predictability and meet the esthetic and functional expectations of the patient. The present study describes a case of a young patient with tooth agenesis of maxillary lateral incisors, which was conducted with an integrated planning. After 5-year follow-up of 2 fixed implant-supported prostheses, clinical and radiographic examination showed the treatment to be successful. (Oral Surg Oral Med Oral Pathol Oral Radiol 2012;114:e22-e28)